A Particle Swarm Optimization Algorithm for Smart Grid Voltage Collapse Path - Jie XU; Shinong WANG (Zhongguo dianli)
With the deep research of smart grid system, an equivalent model of smart grid system is studied for the voltage collapse path of complex smart grid system, and the brittleness relationship of the system is analyzed with AGENT diagram. An particle swarm optimization algorithm for optimizing the collapse paths when brittleness occurs is used to give the influence of the brittleness inside the system on the system’s stability and the solutions to the multiple collapse transmitting paths when brittleness is excited, and the collapse paths are analyzed. Based on the model of a 35kV smart grid primary system, the overall system performance is effectively optimized through prediction and control of the brittleness voltage collapse path of smart grid, which is of great significance to the design and control of the smart grid systems. The results show that the collapse of smart grid system nodes is transmitted between subsystem layers, which leads to the voltage collapse of the whole system.